Socialization of Improving Village E-Catalogs to Increase the Competitiveness of MSMEs in Villages - Maharani, Dewi; Laratmase, Paulus; Hanasi, Raihan A.; Misidawati, Dwi Novaria; Syofya, Heppi (Universitas Pahlawan Tuanku Tambusai, 2024)
Currently, the involvement of MSMEs in the economic development process is very rapid, considering that their level of productivity must continue to be developed alongside large businesses. MSMEs contribute to labor absorption on average by 96.66% of the total national workforce, while large businesses only contribute an average of 3.32% to the national workforce. The high ability of MSMEs to create employment opportunities indicates that MSMEs have considerable potential to be developed throughout the country. However, on the other hand, MSMEs have many obstacles, namely limited working capital, low human resources, and lack of mastery of science and technology. Providing information and market networks, easy access to funding, assistance and increasing information technology capacity are efforts to increase the competitiveness of Indonesian MSMEs. Teluk Karya Village needs technology in the midst of globalization. Most of the problems faced are product marketing and their human resource knowledge is still lacking. This Community Service was carried out in Teluk Karya Village, Lampihong District, Balangan Regency, South Kalimantan. In obtaining the data used were observation and literature study. This service activity is an effort to improve the E-Catalog to increase the competitiveness of MSMEs in Teluk Karya Village, Lampihong District, Balangan Regency, South Kalimantan. This effort was motivated by the lack of implementation of the development of E-catalog technology and information in Teluk Karya Village, Lampihong District, Balangan Regency, South Kalimantan, which resulted in a lack of information on the use of marketing through social media, especially using E-Catalogs which could increase the competitiveness of MSMEs in Teluk Karya Village, District Lampihong is not optimal yet. As a form of the author's thinking, several efforts and breakthroughs are offered, namely: 1.) The role of E-Catalog for the Teluk Karya Village community in increasing the competitiveness of MSMEs in the Village, 2.) Increasing the income of village communities, especially MSME actors, in conducting their businesses so that they can compete well and create sustainable community welfare.